Analysis of Bawaslu's Authority in Handling ASN Neutrality Violations in the 2024 Elections Case Study of Handling ASN Neutrality Violations in Gorontalo City Bawaslu - Arbie, Ikbal; Arti, Asdar; Makkulawuzar, Kingdom (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The importance of the function of elections, especially for changes in the country, is an important basis for many institutions to provide standards for democratic elections. This standard is important because it can be used as a benchmark for the success of the election itself. However, the most important thing of all is that elections must be able to provide guarantees of democratic legitimacy. To achieve this, transparency, accountability, credibility and integrity are needed in the implementation of the election itself so that people trust and believe in the election itself. Until now, effective election supervision is believed to be an instrument capable of providing guarantees for the implementation of democratic elections. This type of research is Sociological Juridical research and the approaches used by researchers in compiling this research are, among others: Statute Approach; case approach (case approach); and Comparative Approach. The results of this research show that in carrying out the supervision stages, Bawaslu has carried out outreach with all ASNs, signed MoU agreements and met with every OPD in every sub-district and neighborhood in Gorontalo City. However, every time the Bawaslu General Election is held, Bawaslu still receives reports of alleged violations from the public that ASN has violated the relevant regulations regarding ASN Neutrality which results in tarnishing democracy in terms of ASN neutrality, this arises because of the existence of inhibiting and supporting factors which can measure how far the success of their role is. owned by Bawaslu in upholding the principle of ASN Neutrality in the 2024 General Election.